Optimization Of Road-Based Mass Transportationroad-Based Mass Transport Optimization (Journal of Namibian Studies : History Politics Culture, 2023)
The development of economic activity in an area/city must be supported by optimal transportation services to make it easier for people to take advantage of these mass transportation services. The existence of mass transportation services greatly affects the level of congestion on the highway. Bus mass transit services have been developed in the Karawang district but are not considered optimal. For this reason, local governments need to optimize mass public transportation to control traffic density on the highway and the efficiency of road use, it is necessary to conduct an assessment to obtain an optimal solution for mass public transportation in Karawang Regency. This study aims to develop recommendations related to efforts that can be made to optimize mass public transportation in the Karawang Regency. Based on the analysis results, several conclusions were obtained: 1) public transportation in Karawang Regency has a load factor of